Antimicrobial Resistance Pattern and Plasmid Profile of Salmonella enterica Isolated from Diarrheal Children in Thi-Qar Province/Iraq - Zaman K. Hanan,; Manal B.Saleh,; Ezat H. Mezal, (University of Thi-Qar Journal of Science, 2020)
The aims of this work were to investigate the antimicrobial pattern and plasmid profile of different antibiotic resistant Salmonella species isolated from diarrheal children in Thi-Qar province and to find a possible relationship between resistance patterns and plasmid profile. Salmonella isolates were tested against 15 commonly used antimicrobial agents using the disc diffusion method to determine the resistance Patterns while plasmid DNA was extracted using alkaline lysis method and separated by agarose gel electrophoresis. all isolates were sensitive to the Amikacin and Gentamycin whereas all isolates were resistances to erythromycin; the most prevalent pattern included resistance to Nalidixic acid (50%) , Cefixim and Cefotaxim (37.5%), and to trimethoprim-sulphamethoxazole, Amoxicillin- clavulanic acid and Ampicillin (33.3%).Furthermore, many isolates were resistant to Tetracycline and Chloramphenicol (29.1%), Ciprofloxacin and Nitrofurantion (25%) and Azithromycin (20.8%), while only 12% of isolates were resistances to Norfloxacin. Plasmid analysis of clinical isolates showed several large and small plasmids were extracted from (91.7%) of the isolates and some isolates carried one or more plasmids.